NOISE EXPOSURE AMONG TRAFFIC POLICE OFFICERS IN KHARTOUM LOCALITY, SUDAN - Abdelrahman A Sliman; Omyma M Ibrahim; Alshebli A Ahmed (European Scientific Journal, ESJ, 2015)
Background: This study reports noise exposure among traffic police officers in Khartoum locality, Sudan. In this study, noise exposure was measured among Traffic Police Officer in Khartoum Locality, Sudan, in May 2010. Objectives: This paper addresses the noise levels, and their negative effects on traffic police officers resulting from its exposure to road traffic noise. Materials and Methods: We conducted a cross-sectional study in twenty two streets points along the Khartoum locality roads. The Khartoum locality roads have heavy traffic during the day, and the noise exposure level among traffic policemen was measured during the time period from 9:00 am to 9:00 pm on working day using a noise dosimeter which reads the noise exposure of a person. Also, 46 traffic police officers working in these points were selected as the study population. Results: The level of noise was ranged from 74.5 to 86.7 dBA. 52.2% have mood characteristic as annoyance, while 26.1% have tinnitus. Conclusion: It was observed that at all points, the level of noise was higher. Major effects of noise among traffic police officer include annoyance and tinnitus. All Traffic Police officers did not used hearing protection devices.